The Influence of E-Money, Debit Cards, and Paylater on the Financial Decisions of FEBI Students at UIN North Sumatra in the Industrial Revolution 4.0 Era - Siregar, Isafitri; Atika; Syahbudi, Muhammad (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This research explores the impact of perceived usefulness (PU), perceived ease of use (PEOU), attitude toward using (ATU), and behavioral intention to use (BI) on the decisions made by FEBI UINSU students in utilizing e-money, debit cards, and paylater services. The study population consisted of all active FEBI students enrolled at the State Islamic University of North Sumatra, totaling 4,523 individuals. A sample of 44 students was selected for the study. Employing a quantitative approach, data were collected using a Likert scale, and analyzed through the IBM SPSS Statistics 25 software. The findings revealed that each independent variable, both individually and collectively, had a significant influence on student decision-making. These results suggest that students’ perceptions of usefulness, ease of use, attitudes, and intentions toward financial technology are key factors in shaping their transaction decisions in the context of the Industrial Revolution 4.0.